ANALISA LINDUNG NILAI ( HEDGING ) EVALUASI ATAS TRANSAKASI DERIVATIF PADA PERUSAHAAN PT. SURYA SEMESTA INTERNUSA TBK. PERIODE TAHUN 2019 - Putri Angellita; Firda Tri Bidandari; Dewi Susianti (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
Hedging is an important approach to managing financial risk in a corporate context. The purpose of hedging is to protect the company's value from fluctuations in prices, interest rates or other risks that could negatively impact the company's financial performance. This study aims to analyze hedging practices in the context of the company PT Surya Semesta Internusa Tbk. This research methodology uses secondary data analysis which includes financial reports, risk reports, and company hedging policies. The results show that PT Surya Semesta Internusa Tbk has adopted a proactive hedging approach in managing financial risk. The company uses various hedging instruments, such as futures contracts, options and swaps, to mitigate the impact of commodity price fluctuations and foreign currency risk on their financial performance. PT Surya Semesta Internusa Tbk actively analyzes and identifies the risks it faces and implements appropriate hedging strategies to manage these risks. This study also reveals that hedging management at PT Surya Semesta Internusa Tbk is based on risk management principles that are integrated into the overall corporate strategy. The company has a structured hedging policy and clear standard operating procedures. In addition, PT Surya Semesta Internus Tbk's team is equipped with the necessary knowledge and skills to implement and monitor hedging effectively. However, this study also identified several challenges faced by PT Surya Semesta Internusa Tbk in implementing hedging. These challenges include the complexity of hedging instruments, market uncertainty, and regulatory changes. PT Surya Semesta Internusa Tbk needs to continue to evaluate and adjust their hedging strategy to overcome this challenge. This research provides better insight into hedging practices in the context of the company PT Surya Semesta Internusa. The results of this study can provide guidance for other companies in developing effective and integrated hedging strategies to manage financial risk and protect company value from adverse market fluctuations.